SEEING THE USE OF FIRST LANGUAGE THROUGH THE EYES OF TEACHER AND STUDENTS - Erwin Rahayu Saputra (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
The use of first language in EFL classroom has long been the subject of much controversy and academic debate in both Second Language Acquisition research literature and educational teaching concerns. Teachers and students have their own reasons and justifications about the use of L1 in the classroom. To that point, this study tries to figure out the reasons of using L1 in EFL classroom from the viewpoint of a teacher and class of students of the study. To gain more insight, this study also captures the students’ perspective of their teacher’s L1 use. The collected data from observation, interview and questionnaire were analyzed using thematic analysis in relation to the concerns of this study. The findings demonstrate the variations of the reasons of using L1 from the two sides perspective and the attitude toward the teachers use of L1 from student viewpoint which both of them could inform the teachers, educators and other researchers about what and how should be conducted next.